2021
DOI: 10.3390/cancers13235938
|View full text |Cite
|
Sign up to set email alerts
|

Local Treatments in the Unresectable Patient with Colorectal Cancer Metastasis: A Review from the Point of View of the Medical Oncologist

Abstract: For patients with isolated liver metastases from colorectal cancer who are not candidates for potentially curative resections, non-surgical local treatments may be useful. Non-surgical local treatments are classified according to how the treatment is administered. Local treatments are applied directly on hepatic parenchyma, such as radiofrequency, microwave hyperthermia and cryotherapy. Locoregional therapies are delivered through the hepatic artery, such as chemoinfusion, chemoembolization or selective intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 238 publications
0
27
0
Order By: Relevance
“…Therefore, during chemotherapy, the changes in liver metastases should be observed and the treatment strategy should be adjusted promptly. Combining guidelines and our center’s clinical experience, this study provides the indications for RFA following NAC [ 15 , 46 , 47 ]. (I) Unresectable liver metastasis resulting from progression after NAC; (II) intraoperative combined hepatectomy; (III) due to the combination of NAC, the diameter of liver metastases could be widened to about 5 cm, and the number of liver metastases could be widened to about 5–7; (IV) patient preferences; (V) World Health Organization (WHO) poor performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, during chemotherapy, the changes in liver metastases should be observed and the treatment strategy should be adjusted promptly. Combining guidelines and our center’s clinical experience, this study provides the indications for RFA following NAC [ 15 , 46 , 47 ]. (I) Unresectable liver metastasis resulting from progression after NAC; (II) intraoperative combined hepatectomy; (III) due to the combination of NAC, the diameter of liver metastases could be widened to about 5 cm, and the number of liver metastases could be widened to about 5–7; (IV) patient preferences; (V) World Health Organization (WHO) poor performance status.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that microwaves can activate immune responses via both thermal and nonthermal effects. As an adjuvant approach, microwave ablation has been widely used in cancer therapy, such as non-small cell lung cancer, hepatic carcinoma, and colorectal cancer [ 24 , 25 , 26 , 27 ]. It has been reported that IL-2 and IFN-γ in plasma increase significantly in patients with non-small cell lung cancer, 1 month after microwave ablation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor diet, lack of physical activity, obesity, drinking alcoholic beverages, and cigarette smoking are risk factors for CRC formation (2,3). Current treatment options such as surgery, chemotherapy, radiotherapy, and target therapy are being used for CRC (4). For improving the prognosis of CRC patients, a strategy to develop effective adjuvant therapies potentiating anti-CRC efficacy of current treatment options is of utmost need (5)(6)(7).…”
mentioning
confidence: 99%